THE IMPORTANCE OF PLANNING TECHNOLOGY IN LAND LEVELING - Узоков Абдували Ортикович; Норов Собиржон Негмуродович (Journals Park Publishing, 2024)
The article discusses the importance of planning work in Uzbekistan. Improving quality planning using a leveling machine.
Keywords: land reclamation, long-basic planners, field planning, land use of irrigated areas, efficiency of using high-speed units.